2010
DOI: 10.1007/s10592-010-0158-9
|View full text |Cite
|
Sign up to set email alerts
|

Historic DNA reveals contemporary population structure results from anthropogenic effects, not pre-fragmentation patterns

Abstract: Contemporary patterns of genetic structure among fragmented populations can either result from historic patterns or arise from human-induced fragmentation. Use of historic samples collected prior to fragmentation allows for the origin of genetic structure to be established and appropriate management steps to be determined. In this study, we compare historic and contemporary levels of genetic diversity and structure of an endangered passerine, the New Zealand mohua or yellowhead (Mohoua ochrocephala), using nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 49 publications
1
24
1
Order By: Relevance
“…While a number of aDNA studies have detected temporal geographic range reductions in vertebrate taxa, and corresponding losses of genetic diversity (De Bruyn et al . ; Tracy & Jamieson ; Shepherd et al . ), few if any have detected such markedly distinct demographic histories in two such proximate and ecologically comparable vertebrate lineages.…”
Section: Discussionmentioning
confidence: 99%
“…While a number of aDNA studies have detected temporal geographic range reductions in vertebrate taxa, and corresponding losses of genetic diversity (De Bruyn et al . ; Tracy & Jamieson ; Shepherd et al . ), few if any have detected such markedly distinct demographic histories in two such proximate and ecologically comparable vertebrate lineages.…”
Section: Discussionmentioning
confidence: 99%
“…; Allendorf et al . ; Tracy & Jamieson ; Rosvold et al . ), but our data does not allow to assess the importance of the recent decline played in the contemporary population structure.…”
Section: Discussionmentioning
confidence: 99%
“…), but our data does not allow to assess the importance of the recent decline played in the contemporary population structure. For instance studies on the Mohua ( Mohoua ochrocephala ) (Tracy & Jamieson ), the Spanish imperial eagle ( Aquila adalberti ) (Martinez‐Cruz et al . ) or the red deer ( Cervus elaphus ) (Rosvold et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several empirical studies of terrestrial vertebrates support this finding and showed that genetic structure between populations fragmented within the last 100 years (e.g. Riley et al ., ; Zellmer & Knowles, ; Tracy & Jamieson, ). Collectively, the results from this study and a recent body of work on similar stream‐inhabiting fishes (i.e.…”
Section: Discussionmentioning
confidence: 99%